New taxa and notes of katydids from the tribe Meconematini (Orthoptera: Meconematinae) from Brunei Darussalam - Tan, Ming Kai; Gorochov, Andrej V.; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2017)
Based on the new material collected in Kuala Belalong in Brunei Darussalam, four new taxa of Meconematini katydids (Orthoptera: Tettigoniidae: Meconematinae) are described here. Three new species from three previously known genera are described: Alloteratura (Alloteratura) belalongensis sp. nov., Leptoteratura (Rhinoteratura) chela sp. nov., and Pseudoteratura (Pseudoteratura) kenuan sp. nov. Moreover, one new genus is erected based on the unique type species which is also new to science: Pulchroteratura huiqing gen. et sp. nov.